Penyisihan Warna dan Zat Organik Pada Air Gambut Secara Koagulasi-Flokulasi dengan Koagulan Belimbing Wuluh - Lisa Asmiyarna; Syarfi Daud; Lita Darmayanti (Jurnal Teknik, 2022)
Peat water has potential as a source of clean water because of its ample availability but qualitatively it still does not meet the standards according to Permenkes No.32 Tahun 2017 quality of clean water, such as organic substances and colors that are still high. This study uses a coagulation-flocculation methods using a Averrhoa bilimbi juice and alum. The variation are dosage averrhoa bilimbi juice (22,5 ml, 25 ml, 27,5 ml) with alum 0,25 gr and pH 4, 5, 6, 7, 8 in setting aside color and organic matter. The results showed that the treatment of peat water in the treatment variation 27,5 ml, alum 0,25 gr and pH condition 4 is already the best result for water quality requirements. Decreasing the colour with value  95,61% and organic substances is about 71,18%.